Pengaruh Gaya Hidup dan Pendapatan terhadap Perilaku Menabung pada Karyawan Klinik Mata Tritya Dimediasi oleh Literasi Keuangan - Esti Sumirat; Siti Mujanah; Achmad Yanu Alif Fianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Saving is a good habit that every individual can do as early as possible, because it needs to be supported by the company. This research investigates the influence of lifestyle and income on financial literacy. Also investigate whether financial literacy is a good mediator. This study conducted a survey of employees at the Tritya Surabaya eye clinic using saturated sampling with 67 respondents. The data was then analyzed using Structural Equation Modeling. The findings show that lifestyle and income make a positive contribution to financial literacy. Research also proves that financial literacy mediates the relationship between lifestyle and income on saving behavior. This study contributes to understanding employee behavior by using a framework of financial literacy and saving behavior in medical companies, which can also be applied to general companies.